2011
DOI: 10.1186/1471-2431-11-84
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of growth and symptoms of attention-deficit/hyperactivity disorder in children: a longitudinal study

Abstract: BackgroundEmpirical evidence suggests that prenatal growth is associated with attention deficit/hyperactivity disorder (ADHD) and its symptoms. Data on the importance of postnatal growth is, however scanty. We studied whether pre- and postnatal growth up to 56 months is associated with symptoms of ADHD in children.MethodA longitudinal regional birth cohort study comprising 893 children followed up to 56 months. The associations between pre- and postnatal growth and parent-rated ADHD symptoms of the child were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
2
26
0
1
Order By: Relevance
“…The children's behavioral symptoms of ADHD were assessed using the parent version of the Conners' Hyperactivity Index [18], which has been widely used in epidemiological and clinical studies [19][20][21] and has previously been validated in preschooled children in China [22,23]. This index comprises ten items rated on a four-point scale (from 0 = not at all to 3 = very much).…”
Section: Adhd Symptoms In Offspringmentioning
confidence: 99%
“…The children's behavioral symptoms of ADHD were assessed using the parent version of the Conners' Hyperactivity Index [18], which has been widely used in epidemiological and clinical studies [19][20][21] and has previously been validated in preschooled children in China [22,23]. This index comprises ten items rated on a four-point scale (from 0 = not at all to 3 = very much).…”
Section: Adhd Symptoms In Offspringmentioning
confidence: 99%
“…Some studies characterized children with ADHD as having lower body weight and height (Spencer et al 1998;Ptacek et al 2009) or body mass index (BMI) (Heinonen et al 2011). Other research shows that stimulant-naïve children with ADHD are characterized by greater body size: they are taller (Swanson et al 2006(Swanson et al , 2007Hanć and Cieślik 2008b), and have higher body weight or BMI (Swanson 2006;Hanć and Cieślik 2008a;Hanć et al 2012) than children without ADHD.…”
Section: Introductionmentioning
confidence: 96%
“…There is very little research focused on assessment of body size of preschool children with ADHD Ebenegger et al 2011;Heinonen et al 2011). This stage of development is especially interesting because it often precedes the moment of formal diagnosis of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…7,28 Studies of postnatal growth and cognitive or behavioral outcomes have focused on weight gain in the first 5 to 12 months of life, not specifically in the neonatal period. [4][5][6][7][8] In general, more rapid postnatal growth among healthy term-born children is linked to better cognitive outcomes. In one of the few studies that explored the early postnatal period, Emond et al 3 showed that children with the lowest 5% of weight gain from birth to 8 weeks had ∼3-point lower IQ scores than the rest of the cohort (n = 7975).…”
Section: Discussionmentioning
confidence: 99%
“…At the extreme, infants with feeding difficulties may be diagnosed with growth faltering (or "failure to thrive"), which has been associated with 3-to 4-point lower IQ scores compared with children without growth faltering. 2,3 Previous studies in nonclinical populations suggest that faster growth in infancy and childhood is associated with better cognitive outcomes, [4][5][6][7][8] although some findings have been null. 9 Disparities in the literature may reflect varying methods of analysis, small sample sizes (resulting in insufficient statistical power), and differences in the age period studied.…”
mentioning
confidence: 99%